Microorganisms isolated from blood cultures in pediatrics clinic - Metin Dogan; Muhammed Yusuf Ozan Avcı; Abdullah Akkus; Mustafa Bulut (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2020)
Because of high mortality and morbidity, identifi cation of microorganisms causing sepsis is important for the treatment of the patient. Blood culture is the most valuable test for diagnosis and treatment. The aim of this study was to evaluate microorganisms isolated from blood cultures retrospectively.